Guidance Counseling Strategies to Overcome Academic Problems of High School Students: Guidance Counseling Strategies to Overcome Academic Problems of High School Students - Andra Saputra; Mega Iswari; Afdal (International Journal of Technology Vocational Education and Training, 2024)
This research aims to identify and develop effective guidance and counseling strategies in overcoming students' academic problems in high school. The research methods used were literature studies and field research to collect data from various relevant sources and reinforced with questionnaire instruments. Based on research findings, several key recommendations have been identified to improve the quality and effectiveness of guidance and counseling services. First, increasing the frequency and quality of counseling through increasing the number of counselors available and further training for counselors to ensure adequate services for all students who need support. Second, the development of a more structured and comprehensive guidance program, covering academic, emotional and social aspects to help students holistically. Third, increase parental involvement in guidance and counseling programs through training or workshops to support their children at home. Fourth, carry out regular evaluations of the effectiveness of the guidance and counseling program to ensure that the program continues to be improved and adapted to student needs. Implementation of these recommendations is expected to improve the quality of guidance and counseling services in high schools and help students overcome their academic problems more effectively.